2022
DOI: 10.21873/invivo.12996
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Active Immunomodulator As a Novel Therapy for an Infectious Bacterial Disease, Buruli Ulcer

Abstract: Background/Aim: Mycobacterium ulcerans causes the necrotizing skin disease Buruli ulcer (BU), characterized by the formation of subcutaneous lesions and immunosuppression thought to be mediated by the virulence factor mycolactone. Since early BU lesions are typically painless, patients often seek standard oral antibiotic therapy at the advanced stages when the treatment is less effective. Given that currently there is no curative topical treatment for BU, our objective was to evaluate a plasma membrane fluidiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…They have observed that DEA inhibits the immunosuppressive activity of M. ulcerans and slows down the appearance of ulcers and new lesions while promoting the healing process. M. ulcerans has an immunosuppressive effect that is mediated by mycolactone and appears to be inhibited by DEA [ 65 ]. In a recent article, poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) microparticles and gellan gum (GG) hydrogel were utilized to incorporate rifampicin and streptomycin for the cutaneous administration of antibiotics in BU.…”
Section: New Therapeutic Strategies For Buruli Ulcermentioning
confidence: 99%
“…They have observed that DEA inhibits the immunosuppressive activity of M. ulcerans and slows down the appearance of ulcers and new lesions while promoting the healing process. M. ulcerans has an immunosuppressive effect that is mediated by mycolactone and appears to be inhibited by DEA [ 65 ]. In a recent article, poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) microparticles and gellan gum (GG) hydrogel were utilized to incorporate rifampicin and streptomycin for the cutaneous administration of antibiotics in BU.…”
Section: New Therapeutic Strategies For Buruli Ulcermentioning
confidence: 99%